Asian management of hypertension: Current status, home blood pressure, and specific concerns in Thailand. Issue 3 (31st January 2020) - Buranakitjaroen, Peera; Wanthong, Sirisawat; Sukonthasarn, Apichard
Abstract: The prevalence of hypertension is increasing, but rates of awareness, treatment, and blood pressure (BP) control are also increasing. In terms of cardiovascular disease, the prevalence of coronary artery disease (CAD) and stroke is similar, but stroke mortality is higher than that from CAD. Home BP monitoring (HBPM) is an important tool for determining the presence of white‐coat or masked hypertension, facilitating drug cost savings or effective cardiovascular risk management strategies, respectively. However, there are a number of barriers to use of HBPM in Thailand. These include lack of availability (particularly in lower socioeconomic groups), lack of awareness of the importance of white‐coat and masked hypertension, and concerns about device reliability. The latest Thai Hypertension Society guidelines recommend that physicians and nurses encourage their patients to use their HBPM devices, and these are increasingly being utilized in clinical practice for both diagnostic purposes and therapeutic monitoring. Calcium channel blockers are the most commonly used antihypertensive agents in Thailand, followed by angiotensin receptor blockers, ß‐blockers, and diuretics. Angiotensin‐converting enzyme inhibitors are used less often due to drug‐related cough, and the use of fixed drug combinations is low because of their high cost and more complex reimbursement process. Ongoing work is needed to improve the primary prevention and effective treatment of hypertension in Thailand.